A Patterned Architecture of Monoaminergic Afferents in the Cerebellar Cortex: Noradrenergic and Serotonergic Fibre Distributions within Lobules and Parasagittal Zones - Longley, Michael; Ballard, John; Andres-Alonso, Maria; Varatharajah, Rebecca Constance; Cuthbert, Hadleigh; Yeo, Christopher H. (Neuroscience, 2021)
•Serotonergic (5-HT) and noradrenergic (NA) afferent systems to the cerebellar cortex have unique and different geometries.•5-HT and NA fibre trajectories are strongly anisotropic and orthogonal to each other.•Each 5-HT afferent runs along the long axis of its cortical folium crossing multiple zones and potentially signals to all.•Each noradrenergic afferent runs parasagittally with small medial–lateral extent and may signal to one or few microzones.•The geometry of these monoaminergic afferent systems suggests very different roles in cerebellar information processing. The geometry of the glutamatergic mossy-parallel fibre and climbing fibre inputs to cerebellar cortical Purkinje cells has powerfully influenced thinking about cerebellar functions. The compartmentation of the cerebellum into parasagittal zones, identifiable in olivo-cortico-nuclear projections, and the trajectories of the parallel fibres, transverse to these zones and following the long axes of the cortical folia, are particularly important. Two monoaminergic afferent systems, the serotonergic and noradrenergic, are major inputs to the cerebellar cortex but their architecture and relationship with the cortical geometry are poorly understood. Immunohistochemistry for the serotonin transporter (SERT) and for the noradrenaline transporter (NET) revealed strong anisotropy of these afferent fibres in the molecular layer of rat cerebellar cortex. Individual serotonergic fibres travel predominantly medial–lateral, along the long axes of the cortical folia, similar to parallel fibres and Zebrin II immunohistochemistry revealed that they can influence multiple zones. In contrast, individual noradrenergic fibres run predominantly parasagittally with rostral-caudal extents significantly longer than their medial–lateral deviations. Their local area of influence has similarities in form and size to those of identified microzones. Within the molecular layer, the orthogonal trajectories of these two afferent systems suggest different information processing. An individual serotonergic fibre must influence all zones and microzones within its medial–lateral trajectory. In contrast, noradrenergic fibres can influence smaller cortical territories, potentially as limited as a microzone. Evidence is emerging that these monoaminergic systems may not supply a global signal to all of their targets and their potential for cerebellar cortical functions is discussed.